Mind maps and network analysis to evaluate conceptualization of complex issues: A case example evaluating systems science workshops for childhood obesity prevention. (June 2018) - Frerichs, Leah; Young, Tiffany L.; Dave, Gaurav; Stith, Doris; Corbie-Smith, Giselle; Hassmiller Lich, Kristen
Highlights: It remains challenging to evaluate changes in how individuals and groups think about complex issues. We introduce an approach to assess individual and group conceptualization using mind maps and network analysis. We illustrate how we used the approach to evaluate adolescent's understanding of obesity. The approach provided insight about changes in youths' conceptual understanding of obesity. The approach is feasible to implement inpractice and can provide evidence about the impact of group facilitation methods. Abstract: Across disciplines, it is common practice to bring together groups to solve complex problems. Facilitators are often asked to help groups organize information about and better understand the problem in order to develop and prioritize solutions. However, despite existence of several methods to elicit and characterize how individuals and groups think about and conceptualize an issue, many are difficult to implement in practice-based settings where resources such as technology and participant time are limited and research questions shift over time. This paper describes an easy-to-implement diagramming technique for eliciting conceptualization and a flexible network analysis method for characterizing changes in both individual and group conceptualization. We use a case example to illustrate how we used the methods to evaluate African American adolescent's conceptual understanding of obesity before and after participating in a series of four systems thinking workshops. The methods produced results that were sensitive to changes in conceptualization that were likely driven by the specific activities employed during the workshop sessions. The methods appear strong for capturing salient levels of conceptualization at both individual and collective levels. The paper concludes with a critical examination of strengths and weaknesses of the methods and implications for future practice and research.